7
$\begingroup$

I would please like some help with solving the following equation:

$$z^4 - 2z^3 + 9z^2 - 14z + 14 = 0$$

All I know about the equation is that there is a root with the real part of $1$.

My approach has been to factor out the root: $1 + yi$ and divide the equation with it. The following calculations (using the division algorithm) is quite cumbersome, and I wonder if there is any better way of doing this?

Thank you kindly for your help!

$\endgroup$
5
  • $\begingroup$ Have you plugged $1 + y i$ into the equation and seen what $y$ has to be? $\endgroup$ – muzzlator Feb 24 '13 at 11:28
  • $\begingroup$ No I have not done that, but I can clearly see how that would be a reasonable thing to do :), Thanks for the hint! $\endgroup$ – Lukas Arvidsson Feb 24 '13 at 11:31
  • $\begingroup$ Take a look at the formula for the quartic equation. $\endgroup$ – vonbrand Feb 24 '13 at 11:35
  • $\begingroup$ If it has rational roots they must be $\pm 1$, $\pm 2$ or $\pm 14$. Have you checked those? $\endgroup$ – vonbrand Feb 24 '13 at 11:38
  • $\begingroup$ No probs lukas, I ended up typing up a solution anyway so read below if you get stuck $\endgroup$ – muzzlator Feb 24 '13 at 11:38
6
$\begingroup$

As the coefficients of the different powers of $z$ are real,

if one of the four roots is $1+yi,$ the other must be its conjugate $1-yi$ .

If the other two roots are $x,w,$

then using Vieta's Formulas for the coefficient of $z^3$, $1+yi+1-yi+x+w=2\implies w=-x$

So, $$(z-x)(z+x)\{z-(1+yi)\}\{z-(1-yi)\}=0$$

$$\implies (z^2-x^2)(z^2-2z+1+y^2)=0$$

$$\implies z^4-2z^3+z^2(1+y^2-x^2)+2x^2z-x^2(1+y^2)=0$$

Now compare the coefficients of the different powers of $z$

So, $2x^2=-14,x^2=-7,x=\pm \sqrt{-7}=\pm \sqrt7i$ and $1+y^2-x^2=9\implies 1+y^2+7=9,y^2=1$

So, the roots are $\pm \sqrt7i,1\pm i$

$\endgroup$
2
  • $\begingroup$ Thank you for a great explanation! Much appreciated! $\endgroup$ – Lukas Arvidsson Feb 24 '13 at 12:37
  • $\begingroup$ @LukasArvidsson, my pleasure. Hope I could make the idea clear. $\endgroup$ – lab bhattacharjee Feb 24 '13 at 14:47
8
$\begingroup$

Choosing $z = 1 + y i$, you obtain the formula:

$$y^4 - 2 i y^3 - 9y^2 + 2 i y + 8 = 0$$

Because $y$ is real, this means that

$$2 y^3 - 2y = 0$$

and

$$ y^4 - 9y^2 + 8 = 0$$

The first equation implies $y = 0, 1, -1$. The second equation implies that $y^2 = 8$ or $y^2 = 1$. Thus we see both $1 + i$ and $1 - i$ are solutions. Factor out the polynomial $(z - 1 + i)(z - 1 - i) = z^2 - 2z + 2$ and you'll find the remaining roots.

$\endgroup$
1
  • $\begingroup$ Thank you for a great answer! $\endgroup$ – Lukas Arvidsson Feb 24 '13 at 12:38
1
$\begingroup$

Maxima tells me the roots are $\pm i \sqrt{7}$, $1 \pm i$. It factors as $(z^2 + 7) (z^2 - 2 z + 2)$.

$\endgroup$
1
  • $\begingroup$ Yes that is correct. Thanks for the answer. $\endgroup$ – Lukas Arvidsson Feb 24 '13 at 12:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.